Impression Management and Interview and Job Performance Ratings: A Meta-Analysis of Research Design with Tactics in Mind - Peck, Jessica A.; Levashina, Julia (Frontiers in Psychology, 2017)
Impression management (IM) is pervasive in interview and job performance settings. We meta-analytically examine IM by self- and other-focused tactics to establish base rates of tactic usage, to understand the impact of tactics on interview and job performance ratings, and to examine the moderating effects of research design. Our results suggest IM is used more frequently in the interview rather than job performance settings. Self-focused tactics are more effective in the interview rather than in job performance settings, and other-focused tactics are more effective in job performance settings rather than in the interview. We explore several research design moderators including research fidelity, rater, and participants. IM has a somewhat stronger impact on interview ratings in lab settings than field settings. IM also has a stronger impact on interview ratings when the target of IM is also the rater of performance than when the rater of performance is an observer. Finally, labor market participants use IM more frequently and more effectively than students in interview settings. Our research has implications for understanding how different IM tactics function in interview and job performance settings and the effects of research design on IM frequency and impact.